DIE PRÄSENZ DER WERTLICHEN CHARAKTERISTIK MACABRE-OBSTINÉ IN DEN SPÄTEN KLAVIERWERKEN VON FRANZ LISZT - Miklós FEKETE (Studia Universitatis Babeş-Bolyai. Musica)
The Presence of the Valuable Features Macabre-Obstiné in the Late Piano Creations by Franz Liszt. This paper proposes to analyze those procedures, compositional techniques and means of artistic expression of Franz Liszt, which are aimed to reflect and to embody the ethical and aesthetic values of macabre and obstiné. The analyzed opuses are four piano dances, dating from Liszt’s late composition period. The piano pieces are: Csárdás macabre, Csárdás obstiné, Mephisto-Walzer Nr. 3 and Bagatelle sans tonalité. These laconic, concentrated and bizarre compositions show also a diabolical virtuosity, due to their Mephistophelian program. A few of the compositional techniques used for the musical expression of the macabre and obstiné character are already known from the Wiemar-period, but there are a few new lisztian procedures, which occur in these late pieces, and which increase progressively the distances between his style and Romanticism.